The Military VSL - Thomas J. Kniesner; Ryan Sullivan; W. Kip Viscusi (Institute of Labor Economics (IZA), 2024)
Our research reviews theory and empirical evidence in the economics literature and provides a standard value of a statistical life (VSL) applicable to the Department of Defense (DOD). We follow Viscusi (2018a) by conducting a meta-analysis consisting of 1,025 VSL estimates from 68 different labor market studies and find a best-set average VSL estimate of 11.8 million (US2021) across all studies. For DOD analysts and practitioners, we advocate using our best-set VSL estimate for the vast majority of benefit-cost analyses (BCAs) within the DOD. In addition to providing a VSL benchmark to use in DOD BCAs, we also breakdown casualty types and provide a range of VSL estimates to use in sensitivity analyses. Employing restricted data from the DOD on over 6,700 U.S. military fatalities in Afghanistan and Iraq from 2001 to 2021 we show that (1) fatalities are highly concentrated among young, white, and enlisted males, and that (2) fatality rates in the Army and Marines are in contrast to the low number of fatalities (less than 5%) in the Air Force and Navy. Applying standard VSL pay grade and income adjustments to U.S. military fatalities in Afghanistan and Iraq, we find adjusted VSL estimates ranging in value from 3.2 million to 27.6 million per statistical life (US2021).
Keywords: H56; I18; J17; J28; 330; military; DOD; VSL